Proteolytic activity characterization of bacteria isolated from Malaysian traditional fermented food - Ismail, Najihah (2014)
Three types of bacteria strains, which are Bacillus sp., Enter ococcus gallinarum and Bacillus thuringiensis have been isolated previously from Malaysian traditional fermented food. The proteolytic activities of the three strains were screened on skim milk agar plate. After 24 hours of incubation at 37°C, proteolytic activity was observed based on holozone formation on the skim milk agar plate with a diameter of 0, 1.9, and 3.2 cm respectively for Bacillus sp., Enter ococcusgallinarum and Bacillus thuringiensis. The proteolytic activities of all the strains were characterized based on optimum temperature, temperature stability, optimum pH, pH stability, substrate specificity and effect of metal ions towards activity. All three strains showed optimum activity at 50°C. The optimum pH for Bacillus sp. and Bacillus thuringiensis were pH 8.5, while Enterococcus gallinarum showed maximum enzyme activity of 0.068±0.003 U/ml at pH 7.5. The proteolytic activity of the bacteria were stable in the temperature range of 30°C to 50°C and exhibited rapiddecrease in activity when incubated at 60°C for 60 minutes. Proteolytic activity of all strains was stable at a broad pH range from pH 4.5 to pH 10.6. The bacteria strains displayed high activity for casein, gelatin and fibrin but showed very low activity forbovine serum albumin. Proteolytic activity of Bacillus sp. was enhanced by Cu2+,Ca2+, Mg2+, Fe2+ and Zn2+, while the proteolytic activity of Enterococcus gallinarum was only slightly enhanced by Zn2+.